Catalytic fast co-pyrolysis of bamboo residual and waste lubricating oil over an ex-situ dual catalytic beds of MgO and HZSM-5: Analytical PY-GC/MS study. (1st May 2017) - Wang, Jia; Zhang, Bo; Zhong, Zhaoping; Ding, Kuan; Deng, Aidong; Min, Min; Chen, Paul; Ruan, Roger
Graphical abstract: Highlights: Catalytic co-pyrolysis of bamboo residual and waste lubricating oil was conducted. MgO was beneficial to deacidification via ketonization and aldol condensation. Dual catalytic bed system exhibited prominent deoxygenation and aromatization. A HZSM-5/MgO mass ratio of 3:2 largely increased the yield of aromatics. Waste lubricating oil leads hydrocarbon pool towards the formation of hydrocarbons. Abstract: Catalytic fast co-pyrolysis (co-CFP) of bamboo residual (BR) and waste lubricating oil (WLO) over dual catalytic beds of MgO and HZSM-5 were carried out in an analytical PY-GC/MS. The effects of pyrolysis temperature, catalyst types, HZSM-5/MgO mass ratio and WLO percentage on products distribution and selectivities of aromatics were investigated. Experimental results revealed that 600 °C promoted the total peak area of volatile matters and accelerated the yields of furans and phenols. Compared to HZSM-5, MgO exhibited pronounced deacidification via ketonization and aldol condensation reactions as the minimum yield of acids (2.116%) and the maximum yield of ketones (28.805%) could be obtained. Furthermore, given the selectivity of phenols, MgO not only spurred the increase of overall phenols yield, but also facilitated the selectivity of light phenols like phenol and 4-methyl-phenol. With respect to the co-CFP of BR and WLO, a HZSM-5/MgO mass ratio of 3:2 largely accelerated the yield of aromatics via Diels-Alder reaction. Simultaneously, the WLO percentage played a vital role in the yield of hydrocarbons (i.e. aromatics + olefins & alkanes), and the maximum yield (70.305%) could be attained at the percentage of 60% as a function of significant activation of hydrocarbon pool.